In the rural schools of Acrelândia, guaranteeing access to the second stage - da Assunção José, Elisabete (2007)
This report describes the Centralized Rural Schools Project (Projeto Escolas Rurais Centralizadas) being carried out in the city of Acrelândia, a latex extractive reserve in the state of Acre. The challenge was to ensure access for adolescents, young people and adults to the second segment of Primary School. Subsistence farming as a sole source of income requires the contribution of children, while at the same time promoting a migration of non-qualified youth to the municipality's center to find new work. The main challenges were the drop-out and failure rates of students and unqualified teachers who are not trained to serve all of the grades at the same time. The project implemented a school transport system and, mainly, reoriented the curriculum towards semester-based module disciplines in addition to holding weekend classes at the school, using a semi-boarding school regime. These initiatives were focused on the Central School for Latex-Workers' Children (Escola Centralizada para Filhos de Seringueiros), the fruit of a partnership between the Municipal Secretary of Education and other government authorities with the organized struggle of the latex-workers, through their trade association.